An Assessment of the Oral and Inhalation Acute Toxicity of Nickel Oxide Nanoparticles in Rats - Tara Lyons-Darden; Jason L. Blum; Mark W. Schooley; Melissa Ellis; Jennifer Durando; Daniel Merrill; Adriana R. Oller (Nanomaterials, 2023)
Nickel oxide nanoparticles (NiO NPs) have been the focus of many toxicity studies. However, acute toxicity studies that identify toxicological dose descriptors, such as an LC50 or LD50, are lacking. In this paper, the acute toxicity of NiO NPs was evaluated in albino-derived Sprague-Dawley rats through OECD guideline studies conducted by both the oral and inhalation routes of exposure. The animals were assessed for mortality, body weight, behavioral observations, and gross necropsy. Results from previously conducted (unpublished) acute inhalation studies with larger NiO microparticles (MPs) are also included for comparison. Mortality, the primary endpoint in acute toxicity studies, was not observed for rats exposed to NiO NPs via either the oral or inhalation exposure routes, with a determined LD50 of >5000 mg/kg and an LC50 > 5.42 mg/L, respectively. Our results suggest that these NiO NPs do not exhibit serious acute toxicity in rats or warrant an acute toxicity classification under the current GHS classification criteria. This aligns with similar results for NiO MPs from this and previously published studies.